Apocalypse as critical dystopia in modern popular music Journal for Religion, Film and Media - Javier Campos Calvo-Sotelo (Journal for Religion, Film and Media, 2019)
The last book of the New Testament has inspired countless narratives and cultural productions. In the realm of popular music the Apocalypse was embraced as synonymous of imminent catastrophe, generating a dystopian discourse. As a tool for analysis, the concept of "critical dystopia" has built a useful bridge between apocalyptic menaces, re-enchantment of the world, and social protest. On the other hand, "authenticity" is a sacred dimension within rock, the antidote of commercialism. This paper has two parts: first a conceptual review of the state of the questions and debate involved; and second, an exposition of selected songs, followed by a summary of their main traits.